Characterization of Pregnancy Specific Protein B (PSPB) from Placenta Foetalis (Cotyledon) Friesian Holstein Cows - Samik, Abdul (Jurnal Kedokteran Hewan, 2008)
This research was aimed to find out a substance that was useful in early pregnancy diagnosis of Friesian Holstein cows. Pregnancy Specific Protein B (PSPB) was isolated, purified and partially characterized from cotyledon Friesian Holstein cows. Characterization of PSPB protein was conducted using SDS-PAGE and Western Blot. Antisera were developed against PSPB and by immunohistochemical techniques the protein was localized to the binucleated cells of the cotyledon. The estimated molecular size of Friesian Holstein cows PSPB was 59.88 kDa with the concentration of PSPB protein in cotyledon was 6480 ng/ml. PSPB protein could induce anti-PSPB antibody with the value of optical density (OD) were 0.1790.0102 (before immunization); 1.4660.3288 (3rd week after immunization); 1.9360.4754 (1st week after booster;) and 2.2560.4842 (2nd week after booster).